Evaluation of different techniques for generating landslide susceptibility map [electronic resource] - Javad Mirnazari, 1972- 598135; Baharin Ahmad, supervisor 266336; Barat Mojaradi, supervisor 598136; Fakulti Geoinformasi Dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Ph.D (Remote Sensing))